A Brief Discussion on the Application of Financial Software in Higher Education Institutions - Ge, Yan (International Journal of Global Economics and Management, 2024)
With the arrival of a new management era and the digital age in higher education, the survival environment, operation, and management models of universities have undergone significant changes. Traditional financial software no longer meets the management needs of modern institutions. By selecting appropriate financial software, universities can accelerate the integration of internal information and the utilization of resources. Among these, cost control is a key financial aspect that universities are currently most concerned about. As the scale of operations expands and the total funding increases, the volume of reimbursement transactions has seen exponential growth. The diversification of financing methods has broadened the scope of economic activities in higher education, directly impacting the financial departments by expanding the scope and content of financial work and increasing the daily accounting tasks. Consequently, the workload has significantly increased. The complexity of financial work in universities has risen, leading to prominent issues such as low business approval efficiency, long wait times for employees, and high pressure on financial audits. The development of financial software has also driven an increasing demand for information technology in financial departments. The traditional reimbursement methods can no longer adapt to the current development status and management needs of universities, making the informatization of financial management an inevitable trend.